Kolloquium anlässlich der Jahrestagung der Deutschen Orient-Gesellschaft am 18. Juni 1966 - Anonymus, A.
Kurzreferate von H. G. Buchholz, P. Calmeyer, E. Heinrich, B. Hrouda, O. von Müller, E. Strommenger-Nagel, W. Nagel, R. Opificius, W. Schirmer.